Pengaruh Perubahan Suku Bunga terhadap Return Saham pada Perusahaan Terdaftar di Bursa Efek Indonesia (2013 – 2016) - Carina Fitri; Artika Putri Aulia; Riska Oktaperina; Gusganda Suria Manda (Masyarakat Ekonomi Syariah Bogor, 2025)
This article examines the relationship between interest rate changes and stock returns of companies listed on the Indonesia Stock Exchange during the 2013–2016 period. The study employs secondary data analyzed using multiple linear regression methods. The findings reveal that changes in interest rates have a significant negative effect on stock returns. Additionally, other factors such as inflation and exchange rates exhibit varying effects depending on the industrial sector. These results highlight the importance of considering sectoral characteristics when analyzing the impact of macroeconomic factors on stock market performance.